Comparison of Visual Evoked Potentials in Patients Affected by Optic Neuritis From Multiple Sclerosis or Neuromyelitis Optica Spectrum Disorder. Issue 1 (March 2022) - Filgueiras, Thiago G.; Oyamada, Maria K.; Hokazono, Kenzo; Cunha, Leonardo P.; Apóstolos-Pereira, Samira L.; Callegaro, Dagoberto; Monteiro, Mário L. R.
Abstract : Purpose: To compare the visual evoked potentials (VEPs) of optic neuritis (ON) patients with multiple sclerosis (MS), neuromyelitis optica spectrum disorder (NMOSD), and controls. To evaluate correlations between VEP and optical coherence tomography (OCT), contrast sensitivity (CS), and automated perimetry. Methods: Fifty-five eyes with ON from 29 patients (MS = 14 and NMOSD = 15) and 57 eyes from 29 controls were evaluated using VEP, automated perimetry, CS, and optical coherence tomography. Three groups were analyzed: 1) MS eyes with history of ON (ON-MS), 2) NMOSD eyes with ON (ON-NMOSD), and 3) healthy controls. Groups were compared and associations between the parameters were tested. Results: Compared to controls, ON-MS eyes showed significantly delayed N75 and P100 latencies when using a medium-sized stimulus (30′), and delayed P100 latency when using a large stimulus (1.5°), but similar amplitudes. Compared to controls, ON-NMOSD eyes showed significantly lower N75/P100 amplitudes (both stimulus sizes) and P100/N135 amplitudes (with the 30′ stimulus), but latencies did not differ, except for a delayed P100 latency with the 30′ stimulus. When comparing the 2 ON groups using the 1.5° stimulus, there was significant delay in P100 latency in ON-MS eyes and a reduction in N75/P100 amplitude in ON-NMOSD eyes. Peripapillary retinal nerve fiber layer, macular inner retinal layers, and CS measurements were significantly smaller in ON patients than in controls. A strong correlation was found between VEP parameters and inner retinal layer thickness in ON-NMOSD eyes. Conclusions: ON-MS eyes had normal amplitude and delayed VEP latency, whereas ON-NMOSD eyes displayed reduced amplitude and preserved latency when elicited by checkerboard stimulus with large 1.5° checks. Under such conditions, VEP may help distinguish resolved MS-related ON from resolved NMOSD-related ON.